The Obligations and Rights to Obtain Compensation as a Result of the Space Objects Discovery - Wulandari, Sinar Aju; Abidin, Izzah Khalif Raihan; Achmad, Zainal Abidin; Prakoso, Muhammad Ardy (Institut Teknologi Sepuluh Nopember, 2023)
Indonesia, as a nation where foreign space objects are discovered, holds the right to seek compensation, thereby addressing the country's claims to reinstate pre-damage conditions. Under international regulations, any country launching objects into outer space from its territory or launch facilities assumes responsibility for damages incurred in other nations. This research employs a qualitative legal research methodology, employing both statutory and conceptual approaches. The statutory method scrutinizes laws pertinent to the identified legal concerns. The primary sources encompass the 1967 Treaty on the Principles Governing State Activities in Space Exploration and Utilization, including the Moon and Celestial Bodies, and Indonesia's Law Number 16 of 2002, Gazette Number 34 of 2002, Supplement State Gazette No. 4195. The study's findings highlight that the 1968 Rescue Agreement broadened a state's obligations concerning astronaut rescue, recovery, and repatriation, extending these responsibilities to encompass the return of space objects for exploration purposes. The repatriation of foreign space objects mandates compensation for any damage resulting from the descent of celestial bodies. Therefore, Indonesia, under international legal frameworks, can pursue restitution for damages caused by space objects from other nations, ensuring accountability and restoration of affected conditions.